Can local data change public policy? participatory mapping and evidence-based advocacy in disaster-prone Indonesian communities - Siti Mahmudah Noorhayati (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Disaster-prone Supiturang Village in Pronojiwo, home to 4,050 residents within the Mount Semeru hazard context, required a mechanism for translating local risk experience into evidence usable in disaster governance. Objective: This community engagement program engaged 40 intended residents, village actors, volunteers, youth, women’s-group representatives, and neighbourhood representatives to develop participatory risk maps and advocacy-oriented recommendations. Method: Using a planning-implementation-monitoring/evaluation design, this program combined baseline surveys, short interviews, attendance sheets, observation checklists, mapping products, product rubrics, FGD notes, and partner-commitment forms to document quantitative and qualitative evidence. Results: Planning documentation specified three coordination meetings, five stakeholder groups, 40 baseline responses, five instruments, and two reflection-forum agendas. The implementation framework comprised one orientation session, three workshops, two mentoring clinics across six weeks, four group maps, one consolidated map, and one recommendation matrix. Implication: Monitoring and evaluation targeted 75% attendance, 70% acceptable outputs, a capacity benchmark from index 100 to at least 120, two validation forums, and one follow-up plan. Novelty: Its novelty lies in integrating participatory spatial evidence, measurable engagement thresholds, mentoring, collective validation, and institutional follow-up without presenting planned indicators as demonstrated policy effects.